Managing Impressions and Relationships on Facebook: Self-Presentational and Relational Concerns Revealed Through the Analysis of Language Style. (June 2013) - Bazarova, Natalya N.; Taft, Jessie G.; Choi, Yoon Hyung; Cosley, Dan
The merging of audiences in social media and the variety of participation structures they present, including different audience sizes and interaction targets, pose questions about how people respond to these new communication situations. This research examined self-presentational and relational concerns through the analysis of language styles on Facebook. The authors collected a corpus of status updates, wall posts, and private messages from 79 participants. These messages varied in certain characteristics of language style, revealing differences in underlying self-presentational and relational concerns based on the publicness and directedness of the interaction. Positive emotion words correlated with self-reported self-presentational concerns in status updates, suggesting a strategic use of sharing positive emotions in public and nondirected communication via status updates. Verbal immediacy correlated with partner familiarity in wall posts but not in private messages, suggesting that verbal immediacy cues serve as markers to differentiate between more and less familiar partners in public wall posts.